Corporate Debt/Equity Ratios and the Korean Financial Crisis - Dickie, Paul (School of Management Working Papers, 2000)
High corporate debt/equity ratios are the key systemic issue in many explanations of the Korean financial crisis. Most analysts argue that high debt/equity ratios were linked with a weak credit culture in the financial sector and poor corporate governance. The facts dispute this. Jn this paper, the high Korean debt/equity ratios are shown to be consistent with the theory of capital structure in the context of asymmetric information and the Government assuming default risk. Korean debt/equity ratios reflect traditional firm behaviour and associated macroeconomic variables. To reduce high debt/equity capital structure, the Government has to transfer default risks back to the market, thereby reducing the moral hazards that determined rational investment behaviour.